At-home Management of Food-induced Anaphylaxis (Actualité en allergologie et en immunologie au Canada, 2024)
Anaphylaxis is an acute, potentially life-threatening, systemic reaction characterized by the involvement of two or more body systems. The National Institute of Allergy and Infectious Diseases and Food Allergy and Anaphylaxis Network (NIAID/FAAN) have well-established criteria for the clinical definition of anaphylaxis. Anaphylaxis is a severe allergic reaction that occurs suddenly after contact with an allergy-causing substance (e.g., peanuts), insect venom or medications (e.g., antibiotics). Anaphylaxis criteria include an acute onset of symptoms (within minutes to several hours) involving the skin, mucosal tissue, or both, which may present with generalized hives, pruritus or flushing, or swollen lips, tongue, and uvula. In addition, one or more of the following must be present: respiratory compromise, reduced blood pressure, or associated symptoms of end-organ dysfunction. Anaphylaxis results in a sudden release of mediators, including, but not limited to, histamine from activated mast cells and basophils following the cross-linking of specific immunoglobulin E. Together with downstream mediators, such as prostaglandin D2, platelet activating factor, and leukotrienes, this reaction manifests clinically through peripheral vasodilation, bronchoconstriction, and increased vascular permeability, presenting as a multi-organ emergency requiring immediate intervention.It is estimated that up to 5% of the population has experienced anaphylaxis, although fatality rates are very low at approximately 0.3% and occur most commonly with drug-induced anaphylaxis. Older age, often consistent with pre-existing comorbidities, and delayed epinephrine administration, pose the most significant risk factors for anaphylaxis fatality. While the global rates of anaphylaxis appear to be on the rise, case fatalities fortunately do not seem to follow this trend.